Norway to Iceland including the Faeroes / published at the Admiralty (Great Britain. Hydrographic Office, 1969)
DECCA chart 6th June 1969 "Decca chart L(D4)" -- lower right corner.; Depths shown by soundings. Color; 1:1,322,000